Research in education and the behavioral sciences : concepts and methods - Mason, Emanuel J.; Bramble, William J. (Madison, WI : Brown & Benchmark Publishers, 1997)
Aims to show the reader what research is, the tools and methods needed to conduct it, how to interpret and report the knowledge obtained, and how society may accept that knowledge. The text includes qualitative research and examples to help the reader appreciate these techniques. An instructor's manual and test item file are also available.
Includes bibliographical references and indexes.
Keywords: Education -- Research -- Methodology; Social sciences -- Research -- Methodology; Psychology -- Research -- Methodology